Isolation and molecular sub typing of salmonella enterica from chicken, beef and street foods in Malaysia - Modarressi, S.; Thong, Kwai Lin (2010)
This study was conducted to determine and identify Salmonella isolated from chicken meat, beef and street food (poultry and beef products) and the genetic diversity of Salmonella by pulsed-field gel electrophoresis (PFGE). Eighty-eight non-repeat Salmonella isolates from 300 food samples were isolated and characterized using conventional culture, biochemical and serological methods and confirmation of Salmonella was determined by polymerase chain reaction (PCR) using specific primers. Among the 88 Salmonella isolates, 11 serovars Corvallis (n = 33), Typhimurium (n = 18), Hadar (n = 7), Enteritidis (n = 5), Weltevreden (n = 5), Agona (n = 5), Newport (n = 4), Albany (n = 3), Istanbul (n = 2), Emek (n = 1) and Wandsworth (n = 1) were identified. All the 88 Salmonella isolates were typable by PFGE with 61 distinct pulsed-field profiles. The cluster analysis indicates that 61 different pulsotypes were separated into groups of identical serovars based on their PFGE profiles. The isolation of various serovars of Salmonella from different sources indicates the presence and distribution of Salmonella in raw meats and street foods. Knowledge of variability of subtypes of different serovars and sources of Salmonella may provide valuable added information for research, risk management, and public health strategies.